2004
DOI: 10.1074/jbc.m403323200
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Antiproliferative Consequences of Activated Polyamine Catabolism in LNCaP Prostate Carcinoma Cells

Abstract: Depletion of intracellular polyamine pools invariably inhibits cell growth. Although this is usually accomplished by inhibiting polyamine biosynthesis, we reasoned that this might be more effectively achieved by activation of polyamine catabolism at the level of spermidine/spermine N 1 -acetyltransferase (SSAT); a strategy first validated in MCF-7 breast carcinoma cells. We now examine the possibility that, due to unique aspects of polyamine homeostasis in the prostate gland, tumor cells derived from it may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 43 publications
4
57
1
Order By: Relevance
“…The effort was catalyzed by our recent reports showing that conditional overexpression of SSAT inhibits in vitro growth of both MCF-7 breast carcinoma cells (20) and LNCaP prostate carcinoma cells (21). Consistent with these findings, we now demonstrate that overexpression of SSAT markedly suppresses tumor outgrowth of early and advanced prostatic cancer in TRAMP mice.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…The effort was catalyzed by our recent reports showing that conditional overexpression of SSAT inhibits in vitro growth of both MCF-7 breast carcinoma cells (20) and LNCaP prostate carcinoma cells (21). Consistent with these findings, we now demonstrate that overexpression of SSAT markedly suppresses tumor outgrowth of early and advanced prostatic cancer in TRAMP mice.…”
Section: Resultssupporting
confidence: 74%
“…As a prelude to the present study, we showed that conditional enzyme overexpression in LNCaP prostate carcinoma cells causes growth inhibition that differed from that seen in MCF-7 cells in that it was not accompanied by polyamine pool depletion (21). Instead cells averted the latter by increasing polyamine biosynthesis at the levels of ODC and AdoMet decarboxylase activities causing heightened metabolic flux through the biosynthetic and catabolic pathways.…”
mentioning
confidence: 83%
See 3 more Smart Citations